Arthur Schnitzler »Das Zeitlose ist von kürzester Dauer.« , Band 2 : Interviews, Meinungen und Proteste (1891-1931) (2023)
The first volume contains almost 90 documented interviews with Arthur Schnitzler. The second volume includes his public expressions of opinion and letters to the editor. Together, they create a 'public biography' of Schnitzler by collecting what the public could know about him. Volume 1: https://e-book.fwf.ac.at/o:1882 Volume 2: https://e-book.fwf.ac.at/o:1881